The Role of Digital Transformation in Shaping Recruitment Strategies and Enhancing Employer Competitiveness in Information Technology Multinationals in India - Samuel, Mark (Digital Repository of Theses, 2026)
“Digital transformation” (DT) has emerged as a formidable change agent of organisational systems, especially in the context of attracting and managing talent by multinationals in IT companies. The purpose of the study is to investigate the role of “Digital Recruitment Technology Adoption” (DRTA), “Data-Driven Talent Acquisition” (DDTA), HR digital capabilities, “Employer Branding” (EB), and strategic talent sourcing on recruitment efficiency, digital talent engagement, and employer competitiveness in global IT organisations in India. The quantitative research design was used to collect the data, a quantitative questionnaire was developed in accordance with the “Technology-Organisation-Environment” (TOE) model, the survey was distributed to 100 HR professionals and managers, and analysed through “descriptive statistics, correlation and multiple regression” in SPSS. Findings indicate that there are high positive correlations between “Digital Recruitment Practices” (DRP) and recruitment efficiency and digital talent engagement, whereas recruitment efficiency and digital engagement are significant positive predictors of employer competitiveness. All in all, the research findings summarise that DT is a significant contributor to achieving recruitment performance and improving the competitive edge of multinational IT businesses in India. Keywords: Digital Transformation, Digital Recruitment Practices, Data-Driven Talent Acquisition, HR Digital Capabilities, Employer Branding, Recruitment Efficiency, Employer Competitiveness, Technology–Organisation–Environment (TOE) Framework, IT Multinational Enterprises